2006
DOI: 10.1107/s1600536806032314
|View full text |Cite
|
Sign up to set email alerts
|

Bis(μ-N,N-diethyldithiocarbamato-κ3S,S′:S′)bis[(μ-N,N-diethyldithiocarbamato-κ2S,S′)silver(II)]

Abstract: Key indicatorsSingle-crystal X-ray study T = 273 K Mean (C-C) = 0.004 Å R factor = 0.021 wR factor = 0.048 Data-to-parameter ratio = 19.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The dihydropyridine ring has a flattened boat conformation. This compares well with the structure of 3-benzotriazol-1-yl-5-tertbutyl-2,6-dimethyl-4-(3-nitrophenyl)-1,4-dihydropyridine-3,5dicarboxylate and nefidipine (Liu et al, 2006;Hofmann & Cimiraglia, 1990;Ramusino & Varì, 1999). The nitro group is found to be disordered.…”
supporting
confidence: 72%
“…The dihydropyridine ring has a flattened boat conformation. This compares well with the structure of 3-benzotriazol-1-yl-5-tertbutyl-2,6-dimethyl-4-(3-nitrophenyl)-1,4-dihydropyridine-3,5dicarboxylate and nefidipine (Liu et al, 2006;Hofmann & Cimiraglia, 1990;Ramusino & Varì, 1999). The nitro group is found to be disordered.…”
supporting
confidence: 72%
“…For related literature, see: Akerströ m (1959); Anacker-Eickhoff et al (1982); Ebihara et al (1994); Fan et al (2004); Liu et al (2006); Song et al (2006); Tang et al (2004); Zhang et al (2002); Greenwood & Earnshaw (1989).…”
Section: Related Literaturementioning
confidence: 99%
“…Since their first description by Akerström (1959) Ag I complexes with dialkyldithiocarbamates have been widely studied owing to their variable coordination modes and, for complexes containing the Ag-Ag metal bonds, also due to their potential photoluminescent properties. Differently substituted alkyl groups and reaction conditions may play crucial roles in the formation of a variety of complexes with unprecedented structures (Ebihara et al, 1994;Liu et al, 2006;Song et al, 2006).…”
Section: S1 Commentmentioning
confidence: 99%
“…For general background, see Akerströ m (1959); Zhang et al (2002); Liu et al (2006); Song et al (2006). For related structures, see: Yin et al (2007); Anacker-Eickhoff et al (1982); Li et al (2005); Greenwood & Earnshaw (1989).…”
Section: Related Literaturementioning
confidence: 99%
“…Synthesis and crystal structure of the Ag(I) complexes with dialkyldithiocarbamates have been widely studied owing to variable coordination configurations since the first description by Akerström (1959). Monomeric, dimeric, hexameric and polymeric structure etc in the Ag(I) complexes have been reported in the past decade years, which was indicated that differently substituted alkyl groups and reaction conditions may play crucial roles in the formation of a variety of complexes with unprecedented structures (Zhang et al, 2002;Liu et al, 2006;Song et al, 2006). We have maintained an interest in silver(I)-dithiocarbamate complexes and report herein the structure of the title compound, [(AgC 15 H 14 NS 2 ) 3 ] n .…”
Section: S1 Commentmentioning
confidence: 99%